Propolis mitigates busulfan-induced testicular dysfunction in rats: insights into redox stabilization, PCNA modulation, and caspase-3 inhibition - AbdAllah, Elham A.; Eid, Basant A.; Hussein, Hassan A.; Abou khalil, Nasser S.; Ragab, Sohair M. M.; Wahman, Asmaa Y.; Almohaimeed, Hailah M.; Moneeb, Rehab H.; Abdel-Tawab, Hanem S.; Mohammedsaleh, Zuhair M.; Barnawi, Jameel; Waly, Hanan S. A. (Frontiers in Pharmacology, 2025)
IntroductionTesticular cytofunctional defects are among the most hazardous effects of cancer chemotherapies. Propolis mitigates the fertility problems associated with gonadotoxic agents through its redox stabilizing, anti-apoptotic, and cytoprotective properties due to presence of bioactive agents identified in our study by gas chromatography–mass spectrometry analysis including, flavonoids, terpenes, aliphatic and aromatic compounds, and amino acids. Herein, we investigated the potential reversal effects of aqueous propolis on busulfan-induced reproductive abnormalities in adult rats.MethodsThirty rats were randomly assigned to five experimental groups, with six animals per group, for duration of 6 weeks. The control group received only the vehicle daily through oral gavage. The DMSO group was given a single intraperitoneal injection of DMSO. The busulfan group received a single intraperitoneal injection of busulfan at a dose of 20 mg/kg body weight, followed by daily oral gavage. The propolis group was administered propolis daily via oral gavage at a dose of 100 mg/kg body weight. In the busulfan + propolis group, rats received a single intraperitoneal injection of busulfan at 20 mg/kg body weight, combined with daily oral gavage of propolis at a dose of 100 mg/kg body weight.Results and discussionBusulfan exposure led to a decrease in serum levels of follicle-stimulating hormone, testosterone, and estradiol 17β, along with an increase in luteinizing hormone. It negatively affected sperm outcomes, causing a decline in sperm count and the percentages of live, normal, and motile sperm, while increasing the percentages of dead and abnormal sperm. Furthermore, busulfan disrupted the testicular defense system, as indicated by elevated testicular malondialdehyde levels and reductions in testicular nitric oxide and reduced glutathione levels, catalase and superoxide dismutase activities, as well as serum total antioxidant capacity. Marked histopathological changes were observed, in concomitant with strong immunoreactivity for proliferating cell nuclear antigen and caspase-3 in germ cells. Propolis supplementation effectively mitigated all these abnormalities in busulfan-intoxicated rats. Propolis is suggested as a potential complementary adjuvant for managing busulfan-induced reproductive dysfunction, owing to its reproductive hormone-modulating, redox-stabilizing, sperm-protective, and anti-apoptotic properties.